Treatment of diarrhea and its differentials among under-five children in Nepal - Joshi, Mili; Aryal, Sukriti; Shrestha, Ira; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: Diarrhea is a leading cause of mortality in under-five children in developing countries. The treatment of diarrhea is critical in reducing the mortality due to diarrhea. Since socio- demographic parameters play a very important role in the implementation of treatment, it is very crucial to take it into consideration while developing national level programs and policies. Methods: The 2011 NDHS data was used in this study. Treatment of diarrhea using various methods were explored first followed by bivariate analysis of treatment of diarrhea with and without any methods as dependent variable and socio-demographic variables of the mother and children as independent variables. Finally, multivariate logistic regression analysis was used to find the independent association of independent variable/s with the dependent variable. Results: Bivariate analysis showed significant association of children’s age and sex, bloody diarrhea, wealth quintiles and ethnicity of mothers on receiving any treatment methods for diarrhea in under-five children. Multivariate analysis revealed independent association of receiving any treatment for diarrhea for children less than six months, male child, women of richer household and dalit caste. Conclusion: It is recommended that the policy makers should focus on female child less than 6 months and women belonging to the dalit caste and living in the poor households while planning for any programs related to treatment of diarrhea in the country.